MODEL PEMBENTUKAN BRAND LOYALTY MELALUI REBRANDING DAN RATIONAL APPEALS - Ken Sudarti; Dewi Zahrotul Munifa Dila (Jurnal Ekonomi dan Bisnis, 2020)
In the competitive telecomunication industry, brand loyalty has become an important issue. Strong brand and marketing activity are becoming one of the critical levers for company’s differentiation and successed. The aim of this study is to find the impact of rebranding and rational appeals on brand loyalty development while using brand image as mediator in Indosat Ooredoo. The sample consist of 100 respondent as Indosat Ooredoo consumer who live in Semarang. Through a structured questionnaire data were collected and with the help of SPSS, analysis was made. The results reveal that rational appeals and rebranding has significant effects on brand image. Rebranding has no impact on brand loyalty, while Indosat Ooredoo’s rational appeals and brand image has significant effect on building consumer’s brand loyalty. In the other side, rational appeals has directly impact on brand loyalty, while rebranding has undirect impact on loyalty throuh brand image as mediator.Keywords: rebranding, rational appeals, brand image, brand loyalty